1987
DOI: 10.1021/ac00144a012
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of selenite and trimethylselenonium ions in urine by anion exchange chromatography and molecular neutron activation analysis

Abstract: A method has been developed for the determination of trimethylselenonium (TMSe) Ion and selenite (Se032™) Ion In urine by anion exchange chromatography, selectively eluting TMSe and Se032'. Since the recoveries are quantitative, a method of additive spikes Is employed to determine TMSe and Se032" Ion concentrations In urine specimens. The TMSe and Se032-chromatographic elutions were collected In vials, Irradiated with neutrons, and radloassayed for 77mSe activity. The limit of detection Is 10 ng of Se as TMSe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…They were also the first to report TMSe in normal human urine (i.e., without selenium supplementation). The data, however, were variable; in one report (25 ) they claimed that TMSe constituted ϳ30% of the total selenium in normal urine, whereas in two other very similar studies (26,28 ), they reported up to 90% TMSe in normal urine.…”
Section: Work Carried Out In the 1980s: Tmse Consolidatedmentioning
confidence: 97%
See 3 more Smart Citations
“…They were also the first to report TMSe in normal human urine (i.e., without selenium supplementation). The data, however, were variable; in one report (25 ) they claimed that TMSe constituted ϳ30% of the total selenium in normal urine, whereas in two other very similar studies (26,28 ), they reported up to 90% TMSe in normal urine.…”
Section: Work Carried Out In the 1980s: Tmse Consolidatedmentioning
confidence: 97%
“…Blotcky and coworkers (25,26,28 ) were especially conspicuous in this area with several publications focusing on determining TMSe with use of neutron activation analysis for detection. They were also the first to report TMSe in normal human urine (i.e., without selenium supplementation).…”
Section: Work Carried Out In the 1980s: Tmse Consolidatedmentioning
confidence: 99%
See 2 more Smart Citations
“…128,129 In all cases trimethylselenonium ion was detectable, but it now seems generally accepted that this ionic species is a major metabolite only when intake of selenium is high. 121,130 Electrothermal atomic absorption spectroscopy (AAS) 131 and molecular neutron activation analysis [132][133][134][135] have been used to analyse metabolites of selenium, including trimethylselenonium ion, in human urine following separation by ion-exchange chromatography. Selenite and selenate in human urine have also been analysed by ICP-AES following separation by a resin complexation method.…”
mentioning
confidence: 99%